Metaverse Effect: Exploring Students’ Vocabulary Achievement, Retention, and Perceptions in Virtual Environments - Elif Ay Kaya; Ceylan Yangın Ersanlı (Journal of Metaverse)
This study sought to examine the effects of Metaverse-based EFL lessons on students’ vocabulary achievement, retention, and perceptions. The participants consisted of 16 EFL high school students who were attending 11th grade during the 2023-2024 academic year in Türkiye. Adopting a sequential explanatory mixed methods research design, this study collected both quantitative data and qualitative data. The quantitative data was collected by vocabulary pre-test, post-test, and delayed post-test, while the qualitative data was obtained through semi-structured interviews to provide more clarification of the quantitative results. The quantitative data was analyzed using descriptive and inferential statistics on the SPSS program, while the qualitative data underwent content analysis. The findings improved students’ vocabulary achievement. However, comparing post-test and delayed post-test results yielded a small but moderately significant decrease in students’ vocabulary retention. The increase in vocabulary achievement in quantitative findings was corroborated by the codes obtained through semi-structured interviews. Accordingly, students perceived that the Metaverse-based EFL classes, which incorporated visual and multimodal resources, as well as competition and interaction, effectively improved their vocabulary growth. In addition, students had positive perceptions of Metaverse as they perceived it as a supplementary educational setting beyond the classroom, which was both relaxing and enjoyable due to its game-like nature. Moreover, it was reported that the use of avatars enhanced their confidence and overall enjoyment. Nevertheless, students identified several drawbacks of the Metaverse, including issues such as overheating of the phone, intermittent voices, and invisibility of some learning materials. This study also offers pedagogical implications for English language teachers regarding the use of Metaverse.